Factors Affecting Dental Students' Comfort with Online Synchronous Learning - David G. McMillan; Olivia R. Kalloo; Roberto A. Lara; Mariana Pavlova; Donna Kritz-Silverstein (MDPI AG, 2022)
Background: The COVID-19 pandemic caused many universities to expand their use of videoconferencing technology to continue academic coursework. This study examines dental students' experience, comfort levels, and preferences with videoconferencing. Methods: Of 100 s-year US dental students enrolled in a local anesthesia course, 54 completed a survey following an online synchronous lecture given in August 2020. Survey questions asked about prior experience with videoconferencing, comfort levels with online and traditional classes, and reasons for not turning on their video (showing their face). Results: Overall, 48.2% had little or no experience with videoconferencing prior to March 2020. Students were more comfortable with in-classroom parameters (listening, asking questions, answering questions, and interacting in small groups (breakouts)) than with online synchronous learning, although differences were not significant (p's > 0.10). Regression analyses showed there were significant positive associations between videoconferencing experience and comfort with both answering questions and interacting in breakouts (B = 0.55, p = 0.04 and B = 0.54, p = 0.03, respectively). Students reported being more comfortable during in-classroom breakouts than in breakouts using videoconferencing (p = 0.003). Main reasons for students not turning on their cameras were that they did not want to dress up (48.1%), other students were not using their video features (46.3%), and they felt they did not look good (35.5%). Conclusions: Dental students were somewhat more comfortable with traditional in-person vs. online classroom parameters. Prior experience with videoconferencing was associated with increased comfort with synchronous learning, suggesting that after the pandemic, it may be beneficial to structure dental school curricula as a hybrid learning experience with both in-person and online synchronous courses.